Nevroendoskopska odstranitev intraventrikelnega hematoma - Koršič, Marjan (Endoskopska revija, 2007)
Evacuation of intraventricular haemorrhage is a new indication for endoscopic neurosurgery. A case of haematocephalus due to rupture of the posterior inferior cerebellar artery aneurysm is presented. A supratentorial intraventricular haematoma was successfully removed neuroendoscopically. This approach can also be used as an effective technique of intraventricular haematoma evacuation.
Keywords: neurology; nevrologija; krvavitev; hematom; endoskopska kirurgija; drenaža